Guar gum-g-poly(N-acryloyl-L-phenyl alanine) based pH responsive smart hydrogels for in-vitro anticancer drug delivery. Issue 3 (3rd July 2022) - Ramani, Jalababu; Alle, Madhusudhan; Sharma, Garima; Reddy, K.V.N. Suresh; Park, Yeongmin; Rao, K.S.V. Krishna; Kim, Jin-Chul
ABSTRACT: In this study, modified natural polymeric-based pH-responsive hydrogels (GNAHs) were formulated using guar gum-grafted-poly(N-acryloyl phenyl alanine), 2-hydroxy ethyl acrylate, and 2-acrylamido-2-methyl-1-propane sulfonic acid. GNAH hydrogels were synthesized using a single-step radical polymerization reaction using N, N'-methylenebisacrylamide as a crosslinker and potassium persulfate as an initiator. The GNAH was used for the controlled release of Imatinib mesylate (IMS), an anticancer drug. The FTIR spectroscopy confirmed the IMS loading as well as grafting reaction between GG-g-PNPA and PHEA-co-PAMPS. This was further confirmed by XRD and DSC studies. The IMS also reduced the negative surface charge of the GNAH hydrogel. The microscopic images showed that the GNAH hydrogels have porous and canal structures with IMS molecules entrapped within the pores. The mode of drug release mechanism was assessed by applying various kinetic equations (non-Fickian diffusion mechanism, Higuchi square root and Korsmeyer–Peppas kinetic models) that showed pH-dependent drug release of hydrogels exhibiting an excellent controlled-release pattern for IMS for more than 48 h. Based on the drug release behavior of the as-synthesized amino acid-functionalized hydrogel, it can be suggested that GNAH hydrogels could also be used as a potential pH-responsive anticancer drug delivery system for other anticancer drugs.